Depression, anxiety and stress assessment in women with polycystic ovary syndrome attending a tertiary care hospital in Bangladesh - Haseen, Fariha; Selim, Shahjada; Kazal, Rezaul Karim; Ahsan, Mohammad Shamsul; Akter, Nurjahan; Hedayet, Hridi; Haney, Umme; Nasrin, Begum; Islam, Syed Shariful (Bangabandhu Sheikh Mujib Medical University Journal, 2025)
Background: This study evaluated depression, anxiety, and stress in women with polycystic ovary syndrome (PCOS) using the depression, anxiety, and stress scale-21 (DASS-21) and examined their live experiences with this endocrine disorder. Methods: A mixed-methods study, combining an analytical cross-sectional study and qualitative grounded theory, was conducted from February to June 2022 at Bangabandhu Sheikh Mujib Medical University. The study involved 266 pre-diagnosed women with PCOS. Psychological symptoms were assessed using the DASS-21. Additionally, 10 in-depth patient interviews and 6 key-informant interviews with mothers explored the personal and societal dynamics of PCOS. Results: The survey revealed significant psychological distress among participants, with 32% as "moderate" for depression, 68% as "extremely severe" for anxiety, and 45% as "severe" for stress. Participants had a mean age of 24.2 years (standard deviation 5.4) and were pre-diagnosed cases of PCOS. Married women had higher odds of anxiety (OR 2.0; 95% CI 1.1‒3.2), while menstrual problems predicted both anxiety (OR 2.0; 95% CI 1.0‒3.4) and stress (OR 2.0; 95% CI 1.0‒3.4). Insomnia significantly predicted anxiety (OR 3.0; 95% CI 1.4‒6.2) and stress (OR 2.3; 95% CI 1.1‒5.1). Societal stigma compounded these challenges, with unmarried girls concerned about acne and hirsutism, and their mothers focusing on menstrual irregularities and fertility. Married women delayed care-seeking by 2–3 years, driven by infertility concerns, highlighting societal pressures around marriage and childbearing as more significant stressors than PCOS itself. Conclusion: Women with PCOS face significant mental health challenges which are exacerbated by marital status, insomnia, menstrual issues, and societal stigma. Family support plays a role in coping with the condition.